2020
DOI: 10.21203/rs.3.rs-18271/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Education Level as a Predictor of Survival in Patients with Multiple Myeloma

Abstract: Background: Disparities in multiple myeloma (MM) prognosis based on sociodemographic factors may exist. We investigated whether education level at diagnosis influenced Chinese MM patient outcomes.Methods: We performed a multicenter retrospective analysis of data from 773 MM patients across 9 centers in China from 2006 to 2019. Sociodemographic and clinical factors at diagnosis and treatment regimens were recorded, and univariate and multivariate analyses were performed.Results: Overall, 69.2% of patients had… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Chan et al [9] suggested that the variation in survival between ethnic groups is primarily driven by differences in the levels of socioeconomic deprivation, which is consistent with data from the Surveillance, Epidemiology, and End Results (SEER) Program [14]. Education level is an important factor in MM patients' demography and is an independent factor affecting survival outcomes [15]. In our study, higher proportion of patients in the TR group had higher levels of education than that in the non-TR group.…”
Section: Discussionmentioning
confidence: 72%
“…Chan et al [9] suggested that the variation in survival between ethnic groups is primarily driven by differences in the levels of socioeconomic deprivation, which is consistent with data from the Surveillance, Epidemiology, and End Results (SEER) Program [14]. Education level is an important factor in MM patients' demography and is an independent factor affecting survival outcomes [15]. In our study, higher proportion of patients in the TR group had higher levels of education than that in the non-TR group.…”
Section: Discussionmentioning
confidence: 72%
“…Patients treated at LHBCC, established in a self-funding hospital, may attract patients belonging to a higher socioeconomic and education level. Xu et al 39 have previously shown that high education levels may independently predict better survival outcome in patients with PCM in an Asian study. Furthermore, socioeconomic status is a global prognostic factor in PCM survival.…”
Section: Discussionmentioning
confidence: 96%
“…There have been other publications demonstrating that non biologic variables impact survival in multiple myeloma such as level of Education. [13] Lack of a social network has also been implicated in increased mortality in women with breast cancer and how this may occur. [9] Advanced cancer patients with caregivers enrolled in a clinical trial had lower survival than patients without caregivers.…”
Section: Discussionmentioning
confidence: 99%